2001
DOI: 10.3406/ecmed.2001.1907
|View full text |Cite
|
Sign up to set email alerts
|

The seed bank and the between years dynamics of the vegetation of a Mediterranean temporary pool (NW Morocco)

Abstract: La dynamique de la végétation a été étudiée pendant 3 années consécutives sur des quadrats disposés le long de transects permanents et les stocks semenciers dénombrés (1 année) par la méthode de mise en germination dans chacune des 3 ceintures identifiées (centre : Bl, intermédiaire : B2 et périphérique : B3). Dans les stocks semenciers, la richesse spécifique, la densité totale des semences et le pourcentage des annuelles différent significativement entre ceintures, augmentant du centre (Bl) vers la périphéri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…Resource levels are known to influence oviposition behaviour of insects (Blaustein & Kotler, 1993;Srivastava & Lawton, 1998). Agricultural ponds in nature and in mesocosms have higher concentrations of nutrients (Rhazi et al, 2001), which may have overwhelmed any effects produced by the live- Table S1 for full species names James, Koch, & Westlake, 2001;Rhazi, Grillas, Charpentier, & Médail, 2004). Croel and Kneitel (2011a) showed that high nutrient inputs to vernal pool mesocosms (without trampling) could also result in the formation of algal blooms (as also shown here), reducing plant cover by up to 87%.…”
Section: Aquatic Communitysupporting
confidence: 54%
See 4 more Smart Citations
“…Resource levels are known to influence oviposition behaviour of insects (Blaustein & Kotler, 1993;Srivastava & Lawton, 1998). Agricultural ponds in nature and in mesocosms have higher concentrations of nutrients (Rhazi et al, 2001), which may have overwhelmed any effects produced by the live- Table S1 for full species names James, Koch, & Westlake, 2001;Rhazi, Grillas, Charpentier, & Médail, 2004). Croel and Kneitel (2011a) showed that high nutrient inputs to vernal pool mesocosms (without trampling) could also result in the formation of algal blooms (as also shown here), reducing plant cover by up to 87%.…”
Section: Aquatic Communitysupporting
confidence: 54%
“…The ponds were selected based on the high species richness of their propagule bank (forest propagule richness = 46, 52, and 54 species and agricultural propagule richness = 50, 43, and 37 species; Bouahim et al., ; El Madihi et al., ; Rhazi et al., ). From each pond, 2 m² (1 m² of the peripheral zone and 1 m² of the centre) of the upper 3 cm of sediment containing the active seed (Rhazi et al., ) and egg bank (Brendonck & De Meester, ) were collected. The sediment from each of the three ponds per sediment type (hereafter referred to as agriculture or forest ponds) was pooled to homogenise propagule composition in the mesocosms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations